Ijtihad Sebagai Pilar Kelangsungan Hukum Islam di Tengah Perubahan Zaman - Somantri, Yayan; Sucipto, Imam (An-Nisa: Journal of Islamic Family Law, 2024)
Ijtihad is a fundamental pillar in maintaining the continuity of Islamic law, ensuring its relevance amidst the challenges of changing times. Derived from the term jahada, meaning "to strive earnestly," ijtihad empowers scholars to establish rulings when the Qur'an and Hadith provide no direct guidance. This dynamic process allows Islamic law to adapt to contemporary issues such as technological advancements, Islamic finance, human rights, and various social challenges. This article aims to analyze the concept of ijtihad, classical methods such as qiyas (analogy), istihsan (juristic preference), and the practices of the scholars of Medina, as well as their application in modern contexts. Using a qualitative approach based on literature review, the study examines classical and contemporary sources. The findings reveal that ijtihad remains a critical tool for ensuring the flexibility of Islamic law, particularly through the application of maslahah mursalah (consideration of public welfare). By adopting a dynamic yet principled approach, ijtihad serves as a strategic mechanism to address the evolving needs of the Muslim community while upholding core Islamic values.